2020
DOI: 10.1002/aepp.13055
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Market Facilitation Program Payments and their Financial Impact for Illinois, Kansas, and Minnesota Farms

Abstract: The recent infusion of cash into production agriculture due to damages from retaliatory trade actions has been large. Up to $28 billion has been authorized through the Trade Mitigation Program in 2018 and 2019, accounting for a significant share of farm income and providing liquidity in an extended period of low prices. Using farm-level data from Illinois, Kansas, and Minnesota, this research examines the importance of market facilitation program payments in supporting incomes and reducing credit default risk.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 5 publications
(8 reference statements)
1
15
0
Order By: Relevance
“…While the trade war has resulted in substantial economic losses to agriculture, several other factors have also contributed to the sharp crop price declines from the relatively high prices in 2010–2014. Trade aid has provided a large infusion of cash to bolster farm balance sheets (Paulson, Featherstone, and Hadrich ), but not necessarily large enough to restore financial conditions to pre‐2018 levels. If the US and China implement a trade deal and MFP is discontinued, then farm financial conditions could worsen since the MFP payment rates appear to be larger than the impact of the trade war on commodity prices.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…While the trade war has resulted in substantial economic losses to agriculture, several other factors have also contributed to the sharp crop price declines from the relatively high prices in 2010–2014. Trade aid has provided a large infusion of cash to bolster farm balance sheets (Paulson, Featherstone, and Hadrich ), but not necessarily large enough to restore financial conditions to pre‐2018 levels. If the US and China implement a trade deal and MFP is discontinued, then farm financial conditions could worsen since the MFP payment rates appear to be larger than the impact of the trade war on commodity prices.…”
Section: Resultsmentioning
confidence: 99%
“…To examine these disparities we use farm‐level data from the Kansas Farm Management Association (KFMA). For those farms in the KFMA database, the average payment for MFP1 was about $37,000 per farm and for MFP2 was about $58,000 per farm (Paulson, Featherstone, and Hadrich ) . The 90 th percentile for MFP1 payments was about $90,000 and for MFP2 was about $130,000 (Paulson, Featherstone, and Hadrich ).…”
Section: Within‐county Distribution Of Trade Aidmentioning
confidence: 99%
See 2 more Smart Citations
“…Two recent studies have evaluated the impact of the 2018 and 2019 MFPs on the financial situation at the level of the farm. Paulson, Featherstone, and Hadrich (2020) , using farm management association data from Minnesota, Illinois, and Kansas, reported that payments from the 2018 MFP accounted for between 40-60% of average net farm income. These payments were found to substantially improve the financial standing of farms in terms of liquidity, solvency, and debt repayment.…”
Section: Introductionmentioning
confidence: 99%